Non-combustible fiber and preparation method thereof
Through the use of N-ethylamine-based monomers and orthopic acid diocyl polycodicocysts during the fiber preparation process, and gradient heating pre-oxidation treatment, the existing pre-oxygen fiber strength and poor textile performance were solved. , Preparation of high -performance non -burning fiber, realizing the application of textiles into multiple non -combustible fabrics.
Patent Information
- Application Number
- CN202411567948.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-01-28
AI Technical Summary
The existing pre-oxygen fibers have problems such as low strength, high brittleness and poor textile processing performance, and it is difficult to process into non-combustible fabrics. The number of existing non-combustible fabrics is limited, which affects its application.
The N-ethylene amine monomer and the two-butyl polycatic polymerization monomers are used. , Spinning and mechanical properties, and heating pre -oxidation treatment through gradient to shorten the pre -oxidation time to avoid the production of the clue core structure.
Preparation of non -combustible fibers with high pre -oxidation level, strong mechanical properties, and fibrous denseness can be woven into 32 non -combustible fabrics, filling the gaps of domestic ultra -high -performance non -burning fiber, and broadening its application field.
Smart Images

Figure CN119372810A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of new materials, and particularly relates to a non-combustible fiber and a preparation method thereof. Background Art
[0002] Carbon fiber (CFs) is a type of high-performance fiber composed of carbon elements. It has both the inherent properties of carbon materials and the softness of fibers. It has the characteristics of high specific strength, high specific modulus, high temperature resistance, friction resistance, low density, conductivity, shock absorption and corrosion resistance. It is widely used in various fields, especially in the military field, and has become the preferred material for advanced composite materials.
[0003] At present, there are many precursors used to prepare carbon fiber. The commercial application is mainly based on polyacrylonitrile (PAN). After polymerization and spinning, polyacrylonitrile-based raw fibers are produced. After pre-oxidation, carbonization and surface treatment, the raw fibers are used to produce high-performance fiber materials, which account for more than 90% of the global carbon fiber production. Among them, the pre-oxidation process is a key process in the production of polyacrylonitrile-based carbon fiber. By selecting appropriate process conditions, PAN-based pre-oxidized fibers with excellent structure can be prepared. Therefore, the product performance of the pre-oxidized fibers will directly affect the performance of the carbon fiber. The pre-oxidized fibers currently used to prepare carbon fiber are precursors prepared for the production of carbon fiber. They have the disadvantages of low strength, high brittleness, and poor textile processing performance, which makes them unable to be processed into non-combustible fabrics. In addition, the counts of existing non-combustible fabrics are mostly 21, which affects the application of non-combustible fabrics.
[0004] In the prior art, chemical modification is usually performed on polyacrylonitrile precursor fibers during the preparation of pre-oxidized fibers, thereby improving the comprehensive performance of pre-oxidized fibers. For example, Chinese Patent Publication No. CN110305247B discloses a method for preparing high-strength medium-modulus polyacrylonitrile-based carbon fiber precursor fibers by dry-jet wet spinning, which uses copolymerization by adding a second and a third monomer to the acrylonitrile monomer to improve the radial structural uniformity of the fiber during the pre-oxidation process, avoid the formation of a skin-core structure, and improve the mechanical properties of the carbon fiber. However, the above solution still has the following problems: the copolymer monomers usually added are mainly itaconic acid, acrylic acid, acrylamide, etc., but the excessive introduction of the second and third monomers significantly reduces the molecular weight of polyacrylonitrile, the polymerization reaction parameters are many, the repeatability is poor, and it is easy to cause the mechanical properties and process performance of the carbon fiber to decrease, so that the quality of the prepared carbon fiber is low and it is difficult to process it into non-combustible fabrics for use. Therefore, it is necessary to develop a specific non-combustible fiber material to solve the problems existing in the existing pre-oxidized fibers. Summary of the invention
[0005] In view of the problems existing in the prior art, the present invention aims to provide a non-combustible fiber and a preparation method thereof. The non-combustible fiber prepared by the method of the present invention adopts a specific method, has a high pre-oxidation degree, a short pre-oxidation time, strong mechanical properties, and high fiber density, and can be woven into 32-count non-combustible fabrics, filling the gap in domestic ultra-high performance non-combustible fibers.
[0006] To achieve the above object, the present invention provides the following technical solutions: A method for preparing non-combustible fiber comprises the following steps: (1) Preparing polyacrylonitrile spinning solution: acrylonitrile, a second comonomer, dibutyl itaconate and an initiator are mixed and subjected to polymerization reaction, and then filtered, demonified and defoamed to obtain a polyacrylonitrile spinning solution; the second comonomer is an N-vinylamide monomer; (2) Preparing non-combustible fibers: subjecting a polyacrylonitrile spinning solution to spinneret treatment to obtain polyacrylonitrile precursor fibers, soaking the polyacrylonitrile precursor fibers in a 5% by mass cobalt sulfate solution for 5-10 minutes, and then soaking the precursor fibers in a pretreatment solution for 10-15 minutes, and pre-oxidizing the soaked precursor fibers by gradient heating to obtain non-combustible fibers; the pretreatment solution is a mixed aqueous solution of succinic acid and sodium lauroyl methyl taurate.
[0007] In order to solve the defects of low strength and poor textile processing performance of the existing pre-oxidized silk fibers, the present invention adopts N-vinyl acetamide as the second monomer, adds dibutyl itaconate as the third monomer, and adopts a hydrothermal polymerization method to prepare a polyacrylonitrile spinning solution under the action of an initiator. The addition of an amide group can improve the hydrophilicity of the fiber and promote the double diffusion of the fiber. The addition of the third monomer of dibutyl itaconate can regulate the regularity of the molecular chain, reduce the cohesion between macromolecular chains, thereby reducing the crystallinity, and improve the spinnability, stretchability and orientation of the fiber. In the subsequent pre-oxidation stage, a molecular-level channel can be reserved for the diffusion of oxygen from the surface to the inside, thereby slowing down or eliminating the skin-core structure and improving the homogeneity of the pre-oxidation. The second and third monomers are added in a dropwise manner, which can induce and promote the cyclization reaction. Under the same pre-oxidation conditions, the oxidized polyacrylonitrile fiber can reach a higher cyclization degree in a shorter time, avoid the sudden temperature rise and local heat storage of the fiber during pre-oxidation, reduce the chance of the main bond breaking and chain breaking, thereby shortening the time of the pre-oxidation process, reducing the production cost, and maintaining the uniformity and integrity of the fiber structure, thereby improving the fiber quality.
[0008] Preferably, the second comonomer is any one of N-vinylacetamide, N,N'-vinylbisacrylamide and N-ethylacrylamide.
[0009] Preferably, the mass ratio of acrylonitrile, the second comonomer and dibutyl itaconate in step (1) is 97-98:1.6-2.4:0.4-0.6, more preferably 98:1.6:0.4.
[0010] Preferably, the initiator in step (1) is benzoyl peroxide-N,N-diethylaniline, and the solvent is N,N-dimethylformamide or dimethyl sulfoxide.
[0011] Preferably, the polymerization reaction in step (1) comprises the following steps: mixing acrylonitrile and an initiator in a certain proportion and dissolving them in a solvent, mixing the second monomer and dibutyl itaconate and then dropping them into the acrylonitrile mixed solution by a dropwise manner and heating to react for 12-18 hours.
[0012] Preferably, the dripping operation of the second monomer and dibutyl itaconate specifically includes: adding the mixture of the second monomer and dibutyl itaconate in batches, adding 40% of the total mass of the mixture before the polymerization reaction is heated up, and starting to continuously drip the remaining mixture after the temperature is raised to the first stage reaction temperature of the polymerization reaction, and the dripping is completed within 3 hours; the dripping method is adopted to ensure that the second and third comonomers are evenly distributed on each section of the raw silk, ensure the improvement of the overall performance of the non-combustible fiber raw silk, and ensure the stability of the fiber.
[0013] Preferably, the heating reaction specifically comprises the following steps: firstly reacting at 60-70°C for 1-3h in the first stage, and then heating to 70-75°C in the second stage at a heating rate of 0.05-0.15°C / min for 11-15h.
[0014] Preferably, the de-singling in step (1) is carried out in a de-singling tower, and the pressure of the de-singling tower is 0.001-0.002 MPa.
[0015] Preferably, the spinning process in step (2) specifically comprises the following steps: a. The polyacrylonitrile spinning solution is extruded from the spinneret through negative pressure degassing, and the polyacrylonitrile primary fiber is obtained by wet spinning. The process parameters are: the spinneret aperture is 0.07-0.08mm, the coagulation bath is a DMSO aqueous solution with a mass fraction of 50-65%, and the temperature is 45-65℃; b. The desalted water obtained in step (1) is used to remove the solvent from the primary fiber; after desalting the water, two-stage hot water drawing is performed, the first stage hot water temperature is 50-70°C, and the drawing ratio is 1.2-1.5 times; the second stage hot water temperature is 80-95°C, and the drawing ratio is 1.4-1.8 times; c. After hot water drawing, the washed silk is air-dried and then oiled in a silicone oil aqueous solution with an oil mass fraction of 0.55-0.75%; d. The oiled fiber is dried and densified at 142-162° C., and then stretched with high-pressure steam at a steam pressure of 0.45 MPa and a stretching multiple of 3-4 times to obtain the polyacrylonitrile precursor.
[0016] Preferably, the mass concentration of succinic acid in the pretreatment solution of step (2) is 0.2-0.5%, and the mass concentration of sodium lauroyl methyl taurate is 1.0-1.5%. Treating polyacrylonitrile fiber with the pretreatment solution can significantly shorten the reaction time of fiber preoxidation, while improving the tensile strength of the fiber, and will not produce a skin-core structure.
[0017] Preferably, the gradient heating method in step (2) comprises the following steps: firstly, raising the temperature from 25°C to 190-210°C at a heating rate of 3°C / min, and keeping the temperature for 10 min; then raising the temperature to 210-230°C at a heating rate of 2°C / min, and keeping the temperature for 10 min; then raising the temperature to 230-250°C at a heating rate of 1°C / min, and keeping the temperature for 20-30 min; and finally naturally cooling to room temperature.
[0018] Another object of the present invention is to provide a non-combustible fiber. The high-performance non-combustible fiber is prepared by the above-mentioned preparation method. The non-combustible fiber is used for the development of non-combustible, heat-insulating, sound-insulating and thermal-insulating fabrics.
[0019] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention adopts the addition of N-vinyl amide monomers and dibutyl itaconate comonomers. The addition of amide groups can improve the hydrophilicity of the fiber and promote the double diffusion of the fiber. The addition of dibutyl itaconate as the third monomer can regulate the regularity of the molecular chain, reduce the cohesion between the macromolecular chains and thus reduce the crystallinity, improve the spinnability, stretchability and orientation of the fiber, and reserve molecular-level channels for the diffusion of oxygen from the surface to the inside in the subsequent pre-oxidation stage, thereby slowing down or eliminating the skin-core structure and improving the homogeneity of the pre-oxidation.
[0020] (2) The polymerization process of the present invention adopts a staged temperature-controlled polymerization method to improve the uniformity and stability of the polyacrylonitrile fiber liquid; and by adjusting the various parameters of the spraying process and the spinning process, non-combustible fibers with a high degree of pre-oxidation, high fiber density, and high mechanical properties can be produced.
[0021] (3) The present invention conducts an immersion treatment on the polyacrylonitrile precursor, first pre-treating it in a cobalt sulfate solution, and then continuing the treatment in a pre-treatment solution containing succinic acid and sodium lauroyl methyl taurate, which can significantly shorten the pre-oxidation reaction time, inhibit the formation of a skin-core structure, and at the same time improve the tensile strength of the fiber. In addition, no bonding phenomenon occurs during the reaction process, thereby improving the performance of the non-combustible fiber.
[0022] (4) The non-combustible fiber prepared by the present invention has an elongation at break higher than 24%, high tensile strength, excellent fiber properties, and a limiting oxygen index higher than 45%, and can be used to be processed into non-combustible fabrics. In addition, the pre-oxidized silk fiber prepared by the present invention can be used to spin 32-count yarn, while traditional pre-oxidized silk fiber can only spin 21-count yarn, thereby further broadening the application field of the non-combustible fiber. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0024] Figure 1 is a physical picture of the flame-retardant fiber prepared in Example 4 of the present invention; Figure 2 This is a scanning electron microscope (SEM) image of the flame-retardant fiber of Example 4 of the present invention. DETAILED DESCRIPTION
[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. In the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other. Example
[0026] A method for preparing non-combustible fiber comprises the following steps: (1) Preparing polyacrylonitrile spinning solution: 97 parts of acrylonitrile, 1.0 part of N-vinylacetamide, and 0.2 part of dibutyl itaconate are dissolved in 380 parts of N,N-dimethylformamide, and then 20 parts of benzoyl peroxide-N,N-diethylaniline are added and the temperature is raised. When the temperature reaches 60°C, the remaining 1.4 parts of N-vinylacetamide and 0.4 parts of dibutyl itaconate are continuously added dropwise. The addition is completed within 3 hours, and the reaction is carried out at 60°C for 3 hours. Then, the temperature is raised to the second stage of 70°C at a heating rate of 0.05°C / min and the reaction is carried out for 11 hours to obtain a polyacrylonitrile polymer, which is then filtered and subjected to a single-removal treatment to obtain a polyacrylonitrile spinning solution; (2) Preparation of polyacrylonitrile precursor: a. The polyacrylonitrile spinning solution is extruded from the spinneret through negative pressure degassing, and the polyacrylonitrile primary fiber is obtained by wet spinning, the spinneret aperture is 0.07-0.08mm, and the coagulation bath is a DMSO aqueous solution with a mass fraction of 50% and a temperature of 65°C; b. The solvent is removed from the deionized water obtained in step (1); after deionized water, two-stage hot water drawing is performed, the first stage hot water temperature is 50 ° C, the drawing ratio is 1.2 times; the second stage hot water temperature is 80 ° C, the drawing ratio is 1.4 times; c. After hot water drawing, the washed silk is air-dried and then oiled in a silicone oil aqueous solution, with the mass fraction of the oil being 0.55%; d. The oiled fiber was dried and densified at 142°C, and then stretched with high-pressure steam at a steam pressure of 0.45 MPa and a stretching ratio of 3 times to obtain the polyacrylonitrile precursor; (3) Soaking the polyacrylonitrile precursor in a 5% cobalt sulfate solution for 5 minutes, and then soaking it in a pretreatment solution for 10 minutes, wherein the mass concentration of succinic acid in the pretreatment solution is 0.2%, and the mass concentration of sodium lauroyl methyl taurate is 1.0%; (4) Preparation of non-combustible fiber: Place the above-mentioned polyacrylonitrile precursor into an oxidation furnace, raise the temperature in the furnace from 25°C to 190°C in an air atmosphere at a heating rate of 3°C / min, keep warm for 10 min, then raise the temperature to 210°C at a heating rate of 2°C / min, keep warm for 10 min, then raise the temperature to 230°C at a heating rate of 1°C / min, keep warm for 20 min, and naturally cool to room temperature to obtain non-combustible fiber. Example
[0027] A method for preparing non-combustible fiber comprises the following steps: (1) Preparing polyacrylonitrile spinning solution: 98 parts of acrylonitrile, 0.6 parts of N-vinylacetamide, and 0.2 parts of dibutyl itaconate are dissolved in 380 parts of N,N-dimethylformamide, and then 20 parts of benzoyl peroxide-N,N-diethylaniline are added and the temperature is raised. When the temperature reaches 60°C, the remaining 1.0 part of N-vinylacetamide and 0.2 parts of dibutyl itaconate are continuously added dropwise. The addition is completed within 3 hours, and the reaction is carried out at 60°C for 3 hours. Then, the temperature is raised to the second stage of 70°C at a heating rate of 0.05°C / min and the reaction is carried out for 11 hours to obtain a polyacrylonitrile polymer, which is then filtered and subjected to a single-removal treatment to obtain a polyacrylonitrile spinning solution; (2) Preparation of polyacrylonitrile precursor: a. The polyacrylonitrile spinning solution is extruded from the spinneret through negative pressure degassing, and the polyacrylonitrile primary fiber is obtained by wet spinning, the spinneret aperture is 0.07-0.08mm, and the coagulation bath is a DMSO aqueous solution with a mass fraction of 50% and a temperature of 65°C; b. The solvent is removed from the deionized water obtained in step (1); after deionized water, two-stage hot water drawing is performed, the first stage hot water temperature is 50 ° C, the drawing ratio is 1.2 times; the second stage hot water temperature is 80 ° C, the drawing ratio is 1.4 times; c. After hot water drawing, the washed silk is air-dried and then oiled in a silicone oil aqueous solution, with the mass fraction of the oil being 0.55%; d. The oiled fiber was dried and densified at 142°C, and then stretched with high-pressure steam at a steam pressure of 0.45 MPa and a stretching ratio of 3 times to obtain the polyacrylonitrile precursor; (3) soaking the polyacrylonitrile precursor in a 5% cobalt sulfate solution for 10 minutes, and then soaking it in a pretreatment solution for 15 minutes, wherein the mass concentration of succinic acid in the pretreatment solution is 0.5%, and the mass concentration of sodium lauroyl methyl taurate is 1.5%; (4) Preparation of non-combustible fiber: Place the above-mentioned polyacrylonitrile precursor into an oxidation furnace, raise the temperature in the furnace from 25°C to 190°C in an air atmosphere at a heating rate of 3°C / min, keep warm for 10 min, then raise the temperature to 210°C at a heating rate of 2°C / min, keep warm for 10 min, then raise the temperature to 230°C at a heating rate of 1°C / min, keep warm for 20 min, and naturally cool to room temperature to obtain non-combustible fiber. Example
[0028] A method for preparing non-combustible fiber comprises the following steps: (1) Preparing polyacrylonitrile spinning solution: 97.5 parts of acrylonitrile, 0.8 parts of N-vinylacetamide, and 0.2 parts of dibutyl itaconate are dissolved in 380 parts of N,N-dimethylformamide or dimethyl sulfoxide, and then 20 parts of benzoyl peroxide-N,N-diethylaniline are added and the temperature is raised. When the temperature reaches 60°C, the remaining 1.2 parts of N-vinylacetamide and 0.3 parts of dibutyl itaconate are continuously added dropwise. The addition is completed within 3 hours, and the reaction is carried out at 60°C for 3 hours. Then, the temperature is raised to the second stage of 70°C at a heating rate of 0.05°C / min and the reaction is carried out for 15 hours to obtain a polyacrylonitrile polymer, which is then filtered and subjected to a single-removal treatment to obtain a polyacrylonitrile spinning solution; (2) Preparation of polyacrylonitrile precursor: a. The polyacrylonitrile spinning solution is extruded from the spinneret through negative pressure degassing, and the polyacrylonitrile primary fiber is obtained by wet spinning, the spinneret aperture is 0.07-0.08mm, and the coagulation bath is a DMSO aqueous solution with a mass fraction of 50% and a temperature of 65°C; b. The solvent is removed from the deionized water obtained in step (1); after deionized water, two-stage hot water drawing is performed, the first stage hot water temperature is 50 ° C, the drawing ratio is 1.2 times; the second stage hot water temperature is 80 ° C, the drawing ratio is 1.4 times; c. After hot water drawing, the washed silk is air-dried and then oiled in a silicone oil aqueous solution, with the mass fraction of the oil being 0.55%; d. The oiled fiber was dried and densified at 142°C, and then stretched with high-pressure steam at a steam pressure of 0.45 MPa and a stretching ratio of 3 times to obtain the polyacrylonitrile precursor; (3) soaking the polyacrylonitrile precursor in a 5% cobalt sulfate solution for 5-10 minutes, and then soaking it in a pretreatment solution for 10-15 minutes, wherein the mass concentration of succinic acid in the pretreatment solution is 0.2-0.5%, and the mass concentration of sodium lauroyl methyl taurate is 1.0-1.5%; (4) Preparation of non-combustible fiber: Place the above-mentioned polyacrylonitrile precursor into an oxidation furnace, raise the temperature in the furnace from 25°C to 190°C in an air atmosphere at a heating rate of 3°C / min, keep warm for 10 min, then raise the temperature to 210°C at a heating rate of 2°C / min, keep warm for 10 min, then raise the temperature to 230°C at a heating rate of 1°C / min, keep warm for 20 min, and naturally cool to room temperature to obtain non-combustible fiber. Example
[0029] A method for preparing non-combustible fiber comprises the following steps: (1) Preparing polyacrylonitrile spinning solution: 98 parts of acrylonitrile, 0.6 parts of N-vinylacetamide, and 0.2 parts of dibutyl itaconate are dissolved in 380 parts of N,N-dimethylformamide, and then 20 parts of benzoyl peroxide-N,N-diethylaniline are added and the temperature is raised. When the temperature reaches 60°C, the remaining 1.0 part of N-vinylacetamide and 0.2 parts of dibutyl itaconate are continuously added dropwise. The addition is completed within 3 hours, and the reaction is carried out at 65°C for 2 hours. Then, the temperature is raised to the second stage of 75°C at a heating rate of 0.1°C / min and the reaction is carried out for 12 hours to obtain a polyacrylonitrile polymer, which is then filtered and subjected to a single-removal treatment to obtain a polyacrylonitrile spinning solution; (2) Preparation of polyacrylonitrile precursor: a. The polyacrylonitrile spinning solution is extruded from the spinneret through negative pressure degassing, and the polyacrylonitrile primary fiber is obtained by wet spinning, the spinneret aperture is 0.07-0.08mm, and the coagulation bath is a 60% by mass DMSO aqueous solution at a temperature of 55°C; b. The solvent is removed from the deionized water obtained in step (1); after deionized water, two-stage hot water drawing is performed, the first stage hot water temperature is 60 ° C, and the drawing ratio is 1.4 times; the second stage hot water temperature is 90 ° C, and the drawing ratio is 1.6 times; c. After hot water drawing, the washed silk is air-dried and then oiled in a silicone oil aqueous solution, with the mass fraction of the oil being 0.65%; d. The oiled fiber was dried and densified at 152°C, and then stretched with high-pressure steam at a steam pressure of 0.45 MPa and a stretching ratio of 4 times to obtain the polyacrylonitrile precursor; (3) soaking the polyacrylonitrile precursor in a 5% cobalt sulfate solution for 8 minutes, and then soaking it in a pretreatment solution for 12 minutes, wherein the mass concentration of succinic acid in the pretreatment solution is 0.3%, and the mass concentration of sodium lauroyl methyl taurate is 1.3%; (4) Preparation of non-combustible fiber: Place the above-mentioned polyacrylonitrile precursor into an oxidation furnace, raise the temperature in the furnace from 25°C to 200°C in an air atmosphere at a heating rate of 3°C / min, keep warm for 10 min, then raise the temperature to 220°C at a heating rate of 2°C / min, keep warm for 10 min, then raise the temperature to 240°C at a heating rate of 1°C / min, keep warm for 30 min, and naturally cool to room temperature to obtain non-combustible fiber.
[0030] Figure 1 This is a physical picture of the non-combustible fiber prepared in Example 4 of the present invention. Figure 2 This is a scanning electron microscope image. Figure 2 It can be seen that the non-combustible fiber prepared by the present invention has a uniform structure, and from the on-site scanning electron microscope test, it can be seen that the non-combustible fiber prepared by the present invention has no skin-core structure. The present invention uses special mixed monomer copolymerization and improves the radial structural uniformity of the fiber during the pre-oxidation process of polyacrylonitrile-based carbon fiber precursor through special process optimization, avoiding the skin-core structure during the pre-oxidation process, thereby fundamentally improving the mechanical properties of the non-combustible fiber. Example
[0031] A method for preparing non-combustible fiber comprises the following steps: (1) Preparation of polyacrylonitrile spinning solution: 98 parts of acrylonitrile, 0.6 parts of N-vinylacetamide and 0.2 parts of dibutyl itaconate are dissolved in 380 parts of N,N-dimethylformamide, and then 20 parts of benzoyl peroxide-N,N-diethylaniline are added and the temperature is raised. When the temperature reaches 60°C, the remaining 1.0 parts of N-vinylacetamide and 0.2 parts of dibutyl itaconate are continuously added dropwise. The addition is completed within 3 hours, and the reaction is carried out at 70°C (3) for 1 hour. The temperature is then raised to the second stage of 75°C at a heating rate of 0.1°C / min and the reaction is carried out for 11 hours to obtain a polyacrylonitrile polymer. The polyacrylonitrile spinning solution is then obtained by filtration and de-monomerization treatment. (2) Preparation of polyacrylonitrile precursor: a. The polyacrylonitrile spinning solution is extruded from the spinneret through negative pressure degassing, and the polyacrylonitrile primary fiber is obtained by wet spinning, the spinneret aperture is 0.07-0.08mm, and the coagulation bath is a 65% by mass DMSO aqueous solution at a temperature of 45°C; b. The solvent is removed from the deionized water obtained in step (1) of the primary fiber; after deionized water, two-stage hot water drawing is performed, the first stage hot water temperature is 70 ° C, the drawing ratio is 1.5 times; the second stage hot water temperature is 95 ° C, the drawing ratio is 1.8 times; c. After hot water drawing, the washed silk is air-dried and then oiled in a silicone oil aqueous solution with an oil mass fraction of 0.75%; d. The oiled fiber was dried and densified at 162°C, and then stretched with high-pressure steam at a steam pressure of 0.45 MPa and a stretching ratio of 3 times to obtain the polyacrylonitrile precursor; (3) soaking the polyacrylonitrile precursor in a 5% cobalt sulfate solution for 8 minutes, and then soaking it in a pretreatment solution for 12 minutes, wherein the mass concentration of succinic acid in the pretreatment solution is 0.3%, and the mass concentration of sodium lauroyl methyl taurate is 1.3%; (4) Preparation of non-combustible fiber: Place the above-mentioned polyacrylonitrile precursor into an oxidation furnace, raise the temperature in the furnace from 25°C to 210°C in an air atmosphere at a heating rate of 3°C / min, keep warm for 10 min, then raise the temperature to 230°C at a heating rate of 2°C / min, keep warm for 10 min, then raise the temperature to 250°C at a heating rate of 1°C / min, keep warm for 30 min, and naturally cool to room temperature to obtain non-combustible fiber. Example
[0032] A method for preparing non-combustible fiber comprises the following steps: The N-vinyl acetamide in Example 4 is replaced by N,N'-vinyl bisacrylamide, and the remaining method steps are consistent with the method steps in Example 4 to prepare non-combustible fiber. Example
[0033] A method for preparing non-combustible fiber comprises the following steps: The N-vinylacetamide in Example 4 is replaced by N-ethylacrylamide, and the remaining method steps are consistent with the method steps in Example 4 to prepare non-combustible fiber.
[0034] Comparative Example 1 A method for preparing non-combustible fiber comprises the following steps: Compared with Example 4, N-vinylacetamide and dibutyl itaconate were not added, and the remaining method steps were consistent with the method steps in Example 4 to prepare non-combustible fibers.
[0035] Comparative Example 2 A method for preparing non-combustible fiber comprises the following steps: Compared with Example 4, 3 parts by weight of the mixture of N-vinylacetamide and dibutyl itaconate was replaced by itaconic acid, and the remaining method steps were consistent with the method steps of Example 4 to prepare non-combustible fiber.
[0036] Comparative Example 3 A method for preparing non-combustible fiber comprises the following steps: Compared with Example 4, all dibutyl itaconate was replaced by N-vinylacetamide, and the remaining method steps were consistent with the method steps of Example 4 to prepare non-combustible fiber.
[0037] Comparative Example 4 A method for preparing non-combustible fiber comprises the following steps: (1) Preparation of polyacrylonitrile spinning solution: 98 parts of acrylonitrile, 1.6 parts of N-vinylacetamide, and 0.4 parts of dibutyl itaconate were dissolved in 380 parts of N,N-dimethylformamide, and then 20 parts of benzoyl peroxide-N,N-diethylaniline were added and heated to 65°C for 2 hours, and then heated to a second stage of 75°C at a heating rate of 0.1°C / min for 12 hours to obtain a polyacrylonitrile polymer, and then filtered and subjected to a single-removal treatment to obtain a polyacrylonitrile spinning solution; The remaining steps are consistent with the method steps of Implementation 4 to prepare non-combustible fibers.
[0038] Comparative Example 5 A method for preparing non-combustible fiber comprises the following steps: (1) Preparing polyacrylonitrile spinning solution: 98 parts of acrylonitrile, 0.6 parts of N-vinylacetamide, and 0.2 parts of dibutyl itaconate are dissolved in 380 parts of N,N-dimethylformamide, and then 20 parts of benzoyl peroxide-N,N-diethylaniline are added and the temperature is raised. When the temperature reaches 60°C, the remaining 1.0 parts of N-vinylacetamide and 0.2 parts of dibutyl itaconate are continuously added dropwise. The addition is completed within 3 hours, and the reaction is carried out at 65°C for 14 hours to obtain a polyacrylonitrile polymer, which is then filtered and subjected to a single-removal treatment to obtain a polyacrylonitrile spinning solution; The remaining steps are consistent with the method steps of Implementation 4 to prepare non-combustible fibers.
[0039] Comparative Example 6 A method for preparing non-combustible fiber comprises the following steps: (1) Preparing polyacrylonitrile spinning solution: 98 parts of acrylonitrile, 0.6 parts of N-vinylacetamide, and 0.2 parts of dibutyl itaconate were dissolved in 380 parts of N,N-dimethylformamide, and then 20 parts of benzoyl peroxide-N,N-diethylaniline were added and the temperature was raised. When the temperature reached 60°C, the remaining 1.0 parts of N-vinylacetamide and 0.2 parts of dibutyl itaconate were continuously added dropwise. The addition was completed within 3 hours, and the reaction was carried out at 75°C for 14 hours to obtain a polyacrylonitrile polymer, which was then filtered and subjected to a single-removal treatment to obtain a polyacrylonitrile spinning solution; The remaining steps are consistent with the method steps of Implementation 4 to prepare non-combustible fibers.
[0040] Comparative Example 7 A method for preparing non-combustible fiber comprises the following steps: compared with Example 4, the step of soaking the polyacrylonitrile precursor in a cobalt sulfate solution with a mass concentration of 5% for 5-10 minutes in step (3) is omitted, and the polyacrylonitrile precursor is directly soaked in a pretreatment solution for 10-15 minutes. The remaining steps are consistent with the method steps of Implementation 4 to prepare non-combustible fiber.
[0041] Comparative Example 8 A method for preparing a non-combustible fiber comprises the following steps: Compared with Example 4, step (3) is: soaking the polyacrylonitrile precursor in a cobalt sulfate solution with a mass concentration of 5% for 5-10 minutes and then directly proceeding to step (4), omitting the step of soaking in a pretreatment solution, and the remaining steps are consistent with the method steps of Implementation 4 to prepare the non-combustible fiber.
[0042] Comparative Example 9 A method for preparing non-combustible fiber comprises the following steps: compared with Example 4, step (3) is omitted, and the polyacrylonitrile raw fiber is directly pre-oxidized. The remaining steps are consistent with the method steps of Implementation 4 to prepare non-combustible fiber.
[0043] Comparative Example 10 A method for preparing a non-combustible fiber comprises the following steps: compared with Example 4, N-vinylacetamide and dibutyl itaconate are not added, step (3) is omitted, and the polyacrylonitrile raw yarn is directly pre-oxidized. The remaining steps are consistent with the method steps of Implementation 4 to prepare the non-combustible fiber.
[0044] Experimental analysis Effect Example 1 The non-combustible fibers prepared in Examples 1-7 and Comparative Examples 1-10 were subjected to performance tests to measure their linear density and mechanical properties. The test results are shown in Table 1.
[0045] Linear density and diameter: Under the conditions of temperature 20℃ and relative humidity 65%, take 1m long non-combustible fiber, weigh the total mass of the tow, and calculate the linear density of the original fiber.
[0046] Mechanical properties: After the non-combustible fiber was fixed on a rectangular paper with round holes using glue, it was tested using an AGS-X electronic precision universal testing machine with a test gauge length of 18 mm and a crosshead speed of 9 mm / min. Each sample was tested 10 times and the results were averaged to test its breaking strength (cN·dtex -1 ) and elongation at break (%).
[0047] Limiting oxygen index: measured according to the national standard GB / T5454-1997 method.
[0048] Skin-to-core ratio: The skin-to-core ratio was determined by optical microscopy. The non-combustible fibers were embedded in a mixture of epoxy resin and curing agent at a ratio of 15:2 (mass ratio). After curing at 60°C for 2 hours, the fibers were sliced using an EM TRIM2 ultrathin slicer from Leica, Germany. The sample thickness was about 400 nm. The slices were then observed using a 20X objective lens under a BX53M high-power optical microscope from Olympus, Japan. The optical density values were analyzed using ImageJ software based on the different light transmittances of the cortex and core, and the skin-to-core ratio was calculated using the formula: cortex area of the fiber cross section / total area*100%.
[0049] As can be seen from Table 1, from the comparative examples 1-6 experiments, it can be seen that the present invention adds a mixed monomer of N-vinylacetamide and dibutyl itaconate as the second monomer, and the introduction of amide groups can improve the hydrophilicity of the fiber and promote the double diffusion of the fiber. The addition of the third monomer of dibutyl itaconate can regulate the regularity of the molecular chain, reduce the cohesion between the macromolecular chains and thus reduce the crystallinity, improve the elongation at break and the tensile strength of the fiber, improve the mechanical properties of the fiber, and make the fiber have good spinnability, drawability and orientation. It can be seen from comparative examples 4 and 5 that the different polymerization processes also have a great influence on the performance of the prepared non-combustible fiber. The second and third monomers are added in a dropwise manner, which can induce and promote the cyclization reaction. Under the same pre-oxidation conditions, the oxidized polyacrylonitrile fiber can reach a higher degree of cyclization in a shorter time, avoiding the sudden temperature rise and local heat storage of the fiber during pre-oxidation, reducing the chance of rupture of the main bond and chain scission, thereby shortening the time of the pre-oxidation process, reducing the production cost, while maintaining the uniformity and integrity of the fiber structure, thereby improving the fiber quality.
[0050] The experimental results of comparative examples 7-10 show that the embodiments of the present invention pre-treat the polyacrylonitrile precursor with cobalt sulfate solution, succinic acid and sodium lauroyl methyl taurate pre-treatment solution, respectively, which can improve the degree of oxidation of the inner core, eliminate the difference in the skin-core structure from the surface, and increase the skin-core ratio, thereby further improving the limiting oxygen index, increasing the fiber linear density, increasing the elongation at break, and comprehensively improving the performance and quality of the pre-oxidized fiber. Under the same conditions, the pre-oxidation reaction of the unpretreated polyacrylonitrile precursor is not thorough, the skin-core ratio is low, and the skin-core phenomenon is serious, resulting in low tensile strength of the fiber.
[0051] Table 1 Performance test results of non-combustible fiber samples Sample Linear density / dtex <![CDATA[Tensile strength / cN·dtex -1 > Elongation at break / % Limiting oxygen index / % Skin-core ratio / % Example 1 2.1 3.5 24 45 99.5 Example 2 1.8 3.6 26 46 99.4 Example 3 1.9 3.5 25 45 99.7 Example 4 1.7 3.7 28 48 100 Example 5 2.0 3.4 26 45 99.9 Example 6 1.7 3.6 26 46 99.9 Example 7 1.7 3.5 27 47 99.9 Comparative Example 1 2.2 2.3 19 30 67.2 Comparative Example 2 2.1 2.4 17 31 73.5 Comparative Example 3 2.1 3.1 21 33 79.2 Comparative Example 4 2.0 3.3 23 33 87.6 Comparative Example 5 2.1 3.1 24 37 89.1 Comparative Example 6 1.9 3.2 24 36 88.5 Comparative Example 7 2.1 2.7 23 38 72.3 Comparative Example 8 2.0 2.5 22 34 68.9 Comparative Example 9 2.1 2.3 20 33 65.7 Comparative Example 10 1.8 1.9 15 30 30.2 In summary, compared with the control example, the non-combustible fiber prepared by the method of the present invention has high fiber density and higher elongation at break than traditional short fibers, exhibits higher mechanical properties, and a limiting oxygen index higher than 45%. It has excellent non-combustibility and fiber spinnability, and can be directly spun into 32-count silk threads, and then processed into non-combustible fabrics for wide application.
[0052] The above description is only a preferred embodiment of the present invention and is not intended to limit the protection scope of the present invention.
Claims
1. A method for preparing non-combustible fiber, characterized in that: The preparation method comprises the following steps: (1) Preparing polyacrylonitrile spinning solution: acrylonitrile, a second comonomer, dibutyl itaconate and an initiator are mixed and subjected to polymerization reaction, and then filtered, demonified and defoamed to obtain a polyacrylonitrile spinning solution; the second comonomer is an N-vinylamide monomer; (2) Preparing non-combustible fibers: subjecting a polyacrylonitrile spinning solution to spinneret treatment to obtain polyacrylonitrile precursor fibers, soaking the polyacrylonitrile precursor fibers in a 5% by mass cobalt sulfate solution for 5-10 minutes, and then soaking the precursor fibers in a pretreatment solution for 10-15 minutes, and pre-oxidizing the soaked precursor fibers by gradient heating to obtain non-combustible fibers; the pretreatment solution is a mixed aqueous solution of succinic acid and sodium lauroyl methyl taurate.
2. The method for preparing the non-combustible fiber according to claim 1, characterized in that: The second comonomer is any one of N-vinylacetamide, N,N'-vinylbisacrylamide and N-ethylacrylamide.
3. The method for preparing the non-combustible fiber according to claim 1, characterized in that: The mass ratio of acrylonitrile, the second comonomer and dibutyl itaconate in step (1) is 97-98:1.6-2.4:0.4-0.
6.
4. The method for preparing high-performance non-combustible fiber according to claim 1, characterized in that: The polymerization reaction in step (1) comprises the following steps: mixing acrylonitrile and an initiator in a certain proportion and dissolving them in a solvent; mixing a second monomer and dibutyl itaconate and then dropping them into the acrylonitrile mixed solution by a dropwise addition method, and heating the mixture for a reaction of 12-18 hours.
5. The method for preparing the non-combustible fiber according to claim 4, characterized in that: The heating reaction specifically includes the following steps: first, react at 60-70° C. for 1-3 hours in the first stage, and then heat up to 70-75° C. for 11-15 hours in the second stage at a heating rate of 0.05-0.15° C. / min.
6. The method for preparing the non-combustible fiber according to claim 4, characterized in that: In step (1), the initiator is benzoyl peroxide-N,N-diethylaniline, and the solvent is N,N-dimethylformamide or dimethyl sulfoxide.
7. The method for preparing non-combustible fiber according to claim 1, characterized in that: The spinning process in step (2) comprises the following steps: a. The polyacrylonitrile spinning solution is extruded from the spinneret through negative pressure degassing, and the polyacrylonitrile primary fiber is obtained by wet spinning. The process parameters are: the spinneret aperture is 0.07-0.08mm, the coagulation bath is a DMSO aqueous solution with a mass fraction of 50-65%, and the temperature is 45-65℃; b. The desalted water obtained in step (1) is used to remove the solvent from the primary fiber; after desalting the water, two-stage hot water drawing is performed, the first stage hot water temperature is 50-70°C, and the drawing ratio is 1.2-1.5 times; the second stage hot water temperature is 80-95°C, and the drawing ratio is 1.4-1.8 times; c. After hot water drawing, the washed silk is air-dried and then oiled in a silicone oil aqueous solution with an oil mass fraction of 0.55-0.75%; d. The oiled fiber is dried and densified at 142-162° C., and then subjected to high-pressure steam drawing, with a steam pressure of 0.4-0.6 MPa and a steam drawing multiple of 3-4 times, to obtain the polyacrylonitrile precursor.
8. The method for preparing non-combustible fiber according to claim 1, characterized in that: The gradient heating method in step (2) comprises the following steps: firstly, raising the temperature from 25°C to 190-210°C at a heating rate of 3°C / min, and keeping the temperature for 10 min; then raising the temperature to 210-230°C at a heating rate of 2°C / min, and keeping the temperature for 10 min; then raising the temperature to 230-250°C at a heating rate of 1°C / min, and keeping the temperature for 20-30 min; and finally naturally cooling to room temperature.
9. A non-combustible fiber, characterized in that: The non-combustible fiber is prepared by the method according to any one of claims 1 to 8.
10. The non-combustible fiber according to claim 9, characterized in that The non-combustible fiber is used for applications of non-combustible, heat-insulating, sound-insulating and thermal-retaining fabrics.
Citation Information
Patent Citations
A polyacrylonitrile-based carbon fiber precursor polymer and its preparation method, and a polyacrylonitrile-based carbon fiber and its preparation method.
CN110305247B